TELAAH KRITIS PASAL 209 KOMPILASI HUKUM ISLAM INDONESIA TENTANG WASIAT WAJIBAH PERSPEKTIF FIKIH ISLAM - Hidayah, Nur Baiti (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2024)
This article examines Article 209 KHI in Indonesia, regarding the regulation of the share of assets for adopted children and/or adoptive parents. This research aims to explain the differences in giving inheritance or legacy assets intended for adopted children and adoptive parents in Islamic Jurisprudence and KHI in Indonesia. This research is normative research with qualitative descriptive analysis. The results of the research show that in Islamic jurisprudence, if the deceased (heir) does not leave a will for the adopted child or adoptive parents, then there is no will regarding the share of assets for the child or adoptive parents. However, in Article 209 KHI, the provisions for granting mandatory (automatic) wills apply to adopted children or adoptive parents with a maximum share of 1/3 of the testator's inheritance. Understanding the differences in provisions between KHI and Islamic jurisprudence can be analyzed by looking at the context of child adoption in the early days of Islam and the context of adoption in Indonesia. In the early days of Islam, adoption was only aimed at helping the child. However, current adoption practices in Indonesia emphasize the formal legality aspects of adoption. So in practice adoption is mandatory through a court process and has legal consequences, one of which is the share of the heir's inheritance through a mandatory will.